Pemanfaatan teknologi sudah dilakukan di banyak bidang kehidupan seperti sudah banyaknya aplikasi baik berbasis website ataupun android yang menjadi sahabat bagi semua lapisan masyarakat. Sebagian besar masyarakat hanya dapat menggunakan teknologi tersebu - Maria Bellaniar; Andayani, Sri; Wijaya, Andri; Hermawan, Latius (Jurnal Abdimas Musi Charitas, 2021)
The use of technology has been carried out in many areas of life as has been the number of applications based on both websites or android that are friends to all society. Most of the people can only use this technology and a small part of others not only can use but also can make this technology with the help of a programming tool. Self-programming can made with a native concept or the concept of OOP (Object Oriented Programming). Lots of programmers can program with native concepts but not many programmerswho can create programs with the OOP concept. Apart from programmers, there are many students who do not understand the concept of OOP let alone to make it in form a website. Like it or not, these students have to take part in the workshop training on OOP so that knowledge in the IT field can improve. Based on the problem That is, the lecturer service team held a service on Object Training Oriented Programming in Today's Website Development. OOP is a Object-based programming that implements class and object methods as supporters. The dedication carried out is not only a theoretical explanation but also practically so that students can immediately practice what they have explained by the tutor. The result of this activity is that students can make a websites created using OOP and their knowledge and insights about programming can increase.